Comparison of activation energies for the electrical conductivity of silicate glasses obtained by dc and ac techniques - Ziemath, E. C. [UNESP]; Escanhoela, C. A.; Braunger, M. L. (Elsevier, 2017)
The electrical conductivity of glasses with composition (mol%) 22Na2O·8CaO·65SiO2·5MO2 (M = Si, Ti, Ge, Zr, Sn, Ce) was evaluated by two different experimental methods: low-voltage ac impedance and high-voltage dc resistivity. The ac measurements were carried out by the traditional impedance spectroscopy between 90 and 415 °C. In the dc method, a steady-state electric field of about 1 MV/m was applied during 5 s at temperatures between 100 and 210 °C, and the onset current, Io, was measured. Activation energies between 0.71 and 0.81 eV were obtained. The differences between the values obtained by the dc and the ac methods are within experimental errors. The high electric field does not influence the concentration nor the mobility of the charge carriers for these experimental conditions and glass compositions. The dc method applied showed to be a suitable alternative to determine the temperature dependence of the electric conductivity of glasses to further calculation of the activation energy.
Keywords: Activation energy; dc conductivity; Impedance spectroscopy; Silicate glasses